‘Water resource’ framing for the value and governance of glacier water availability in the semi-arid Chilean Andes - Fox, Ellie; Schwartz-Marin, Ernesto; Rangecroft, Sally; Palmer, Steven; Harrison, Stephan (Frontiers in Water, 2024)
Water scarcity associated with glacier retreat in mountainous regions is of growing concern worldwide, especially in arid regions, where precipitation is scarce or seasonal. Scientists and decision makers aim to respond to glacier driven water scarcity by improving glacier protection and developing water resource management strategies. Despite the increasingly prominent ‘water resource’ lens for understanding the changing mountain cryosphere, little research has investigated what this framing means for how different actors value, study, manage, and protect cryospheric water stores. This paper therefore presents a critical analysis of how we conceptualise the importance of glaciers. Specifically, this paper examines how environmental campaigns, scientific research, and policy interact to make glaciers into a water resource, and how this impacts glacier protection. Focusing on a case study of glacier management and protection in the Chilean Andes, the motivations and processes that made glaciers into a water resource in Chile are examined, and the impacts of this for glacier protection in a country where glaciers are exposed to threats from climate change and the mining industry are explored. This paper presents qualitative analysis of interviews conducted with experts in glacier science, policy, and environmental campaigning, and documents associated with managing glaciers as a water resource in Chile. The research shows how, in response to mining threats, glaciers were strategically framed as water resources by environmental campaigners to improve Chilean state protection. This framing was institutionalised within Chile’s water resource management system through science and policy, resulting in some successful protection legislation. However, this resource framing has also integrated glaciers into a system which inherently limits their protection, because their protection is conditional on the shifting ways glaciers are valued for storing and releasing water to downstream communities and ecosystems. Here, we highlight processes that make glaciers into a resource, demonstrate that glaciological knowledge is not directly translated into policy, and importantly, show how managing glaciers as a resource may limit, or even undermine glacier protection efforts. As concern globally grows about water scarcity driven by glacial retreat, these findings are vital for the development of glacier protections and effective management of glacial water.